If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 15 = 4y + 4 Reorder the terms: 15 + 3y = 4y + 4 Reorder the terms: 15 + 3y = 4 + 4y Solving 15 + 3y = 4 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 15 + 3y + -4y = 4 + 4y + -4y Combine like terms: 3y + -4y = -1y 15 + -1y = 4 + 4y + -4y Combine like terms: 4y + -4y = 0 15 + -1y = 4 + 0 15 + -1y = 4 Add '-15' to each side of the equation. 15 + -15 + -1y = 4 + -15 Combine like terms: 15 + -15 = 0 0 + -1y = 4 + -15 -1y = 4 + -15 Combine like terms: 4 + -15 = -11 -1y = -11 Divide each side by '-1'. y = 11 Simplifying y = 11
| 7h+3h-4=-44 | | z-45/8=153/8 | | 3x-32=2x+28 | | y=-2*8-7 | | 79=-2-9r | | -8a(2a+6)=4-a | | y=-2*-2-7 | | -5x-2(4x+2)=-108 | | 1/9y=-6 | | 0.3(x-0.3)=0.6 | | K+765/14=26 | | y=-2*-5-7 | | 0.5x+0.5=2x-7 | | -8+7x=7+3a | | -24-36= | | 4(x+11)=-108 | | 2p-14=1 | | 2/3m=22 | | 1/7m=20 | | 45x+120=85x | | y-70=17/2(x-0) | | -12y-3y= | | 45x+120=85 | | 2(3x-6)=-49 | | 13h-11h=10 | | y=-1+2 | | 4(3x+7)=5(2x-6) | | -19z+7z+6=-18 | | -1/3u=10 | | 1-m/1+m=2/3 | | 6=10(x-10)+4-8x | | -1/5p=-16 |